2019
DOI: 10.1210/js.2018-00427
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hashimoto Thyroiditis on Thyroid Nodule Cytology and Risk of Thyroid Cancer

Abstract: Context The impact of Hashimoto thyroiditis (HT) on the risk of thyroid cancer and its accurate detection remains unclear. The presence of a chronic lymphocytic infiltration imparts a logical mechanism potentially altering neoplastic transformation, while also influencing the accuracy of diagnostic evaluation. Methods We performed a prospective, cohort analysis of 9851 consecutive patients with 21,397 nodules ≥1 cm who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 33 publications
1
47
1
Order By: Relevance
“…This is a prospective cohort study of 10,054 consecutive adult patients with thyroid nodules >1 cm who were evaluated between 1995 and 2017 at the Brigham and Women's Hospital Thyroid Nodule Clinic (3). All patients underwent sonographic and clinical assessment.…”
Section: Methodsmentioning
confidence: 99%
“…This is a prospective cohort study of 10,054 consecutive adult patients with thyroid nodules >1 cm who were evaluated between 1995 and 2017 at the Brigham and Women's Hospital Thyroid Nodule Clinic (3). All patients underwent sonographic and clinical assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Thyroiditis related focal inhomogeneity appeared to be a differential diagnostic entity related to systematic CAD system misdiagnosis, i.e., false-positive detection, since the CAD system appreciated them as a nodule and almost always assigned them a K-TIRADS score of 5 due to "ill-defined borders" and "hypoechogenicity". In clinical practice, especially with less experienced users, such false-positive misdiagnoses may lead to high rates of unnecessary FNAB indications, keeping the high incidence of chronic thyroiditis in mind [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…To cite an example, the differentiation of a nodule from a pseudonodule or focal parenchymal inhomogeneity may be challenging in chronic or subacute thyroiditis [37][38][39][40][41]. This, in turn, is a very common and important clinical problem, since autoimmune thyroiditis has a very high (up to 20%) prevalence and is also widely believed to pose a higher risk regarding thyroid malignancies [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al performed a prospective, cohort study containing 9851 consecutive patients with 21,397 nodules, and they found that the malignant risk of nodules in HT patients is 1.6 times higher than that in non-HT patients. Another study has shown that HT leads to a 3-fold increase in malignant risk compared with non-HT thyroid diseases and that the lymph node metastasis risk is four times greater than that in non-HT patients [ 12 , 13 ]. Therefore, blockade of HT at the source has important significance on decreasing prevalence and progression of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%